Evaluasi Tata Kelola Sistem Informasi Akademik Berbasis COBIT 5 di Universitas Pendidikan Ganesha - I Gusti Lanang Agung Raditya Putra; Benyamin Langgu Sinaga; Irya Wisnubhadra (Universitas Atma Jaya Yogyakarta, 2015)
Abstract. This research is aimed to evaluate the maturity level of IT governance in the implementation of academic information system services at Universitas Pendidikan Ganesha. The method employed is a mix of quantitative and qualitative methods by using a questionnaire, interview, and document research. The foci of this research are in several domains of COBIT 5 including, EDM4, APO7, and BAI4. Source of data obtained from the chair person of the computer center office, the IT staff on computer center office, the IT staff on faculty, and the vice dean of academic affairs. The analysis was done by descriptive interpretative based on COBIT 5. Research results show that IT governance on academic information system services at Universitas Pendidikan Ganesha operates quite well as the maturity level currently reaches level 3 (established). This result is compared with the expected maturity level of 5 (optimizing), the comparison of the result is obtained by the value of the gap. The value of the gap is used to formulate recommendations for improvement. For the improvement of IT governance it is recommended that agencies to prepare competent human resources, as well as documenting every evaluation activities, directing, and monitoring the management of academic information system.Keywords: IT Governance, COBIT 5, Maturity Level.Â Abstrak. Penelitian ini bertujuan untuk mengevaluasi tingkat kematangan tata kelola teknologi informasi (TI) dalam penerapan layanan sistem informasi akademik (SIAK) di Universitas Pendidikan Ganesha. Metode yang digunakan adalah metode campuran kuantitatif dan kualitatif menggunakan instrumen kuesioner, wawancara, dan studi dokumen. Fokus penelitian ini pada beberapa domain COBIT 5 meliputi, EDM4, APO7, dan BAI4. Sumber data diperoleh dari Kepala Pusat Komputer (Puskom), staf TI Puskom, staf TI fakultas, dan pembantu dekan I. Analisis penelitian dilakukan dengan cara deskriptif interpretatif berbasis COBIT 5. Hasil penelitian menunjukkan tingkat kematangan tata kelola TI pada layanan SIAK Undiksha saat ini berada pada tingkat tiga (established). Hasil ini dibandingkan dengan tingkat kematangan yang diharapkan yaitu tingkat lima (optimizing), dari hasil perbandingan tersebut diperoleh nilai kesenjangan. Nilai kesenjangan digunakan untuk merumuskan rekomendasi perbaikan. Untuk perbaikan tata kelola TI disarankan agar lembaga mempersiapkan SDM yang kompeten, serta mendokumentasikan setiap kegiatan evaluasi, pengarahan, dan monitoring dalam pengelolaan SIAK.Kata Kunci: Tata Kelola TI, COBIT 5, Tingkat Kematangan